Inisiasi Pembentukan Angkatan Siber dan Digital dalam Organisasi Tentara Nasional Indonesia - Nurmaida Delviana (Syntax Corporation Indonesia, 2024)
In the era of digital transformation, every country in the world must be able to adapt and adopt these changes as a strategy to strengthen national defense because cyberspace in relation to international relations can be a source of various potential threats, vulnerabilities, and insecurity in the international order. China recognized the importance of AI in shaping the future global economic, military and geopolitical environment, and launched the